Pengaruh Gaya Kepemimpinan Otoriter, Reward dan Punishment Terhadap Kinerja Karyawan Badan Pertahanan Nasional Kabupaten Malang - Hariawan, Bima Pratama; Hidayati, Nur; Amin, Muhammad Sirojuddin (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to find out and analyze how big the influence of Authoritarian Leadership Style, Reward and Punishment is on the Performance of Malang Regency National Defense Agency Employees. The population in this study were non-ASN employees of the Malang Regency National Land Agency. The data collection method in this research used a questionnaire with a sample size determined using the Slovin formula and the results obtained were 83 respondents. Data testing techniques used in this research include validity test, reliability test, normality test, classical assumption test, multiple linear regression test, f test, t test and coefficient of determination test (R2). The results of this research simultaneously show the influence of authoritarian leadership style, rewards and punishment on the performance of employees at the Malang Regency National Defense Agency. Partially, the Authoritarian Leadership Style and Rewards influence the performance of Malang Regency National Defense Agency employees, while Punishment has no effect on the Malang Regency National Defense Agency employee performance. Keywords: Authoritarian Leadership Style, Reward and Punishment on Employee Performance.